AN ANALYSIS OF STUDENTS’ SPEAKING ANXIETY TOWARD THEIR SPEAKING SKILL IN SMKN 3 SIDRAP - Rambung, Herna; Hambing, Agus (Prodi Pendidikan Bahasa Inggris, FKIP, LP3M Universitas Muhammadiyah Sidenreng Rappang, 2024)
This article points out the results of the study attempting to analyze the students speaking anxiety at students in one of SMKN 3 Sidrap. For the purpose of the topic, 28 fellow students were selected as the sample. Research method was quasi-experimental design with two way ANOVA. It was conducted for about four months. According to the results of speaking test, findings showed that using Communicative Language Teaching (CLT) had positive meaningful effect on improving students’ speaking skill viewed from different speaking anxiety. To sum up, CLT is an effective method to teach students’ speaking skill viewed from different speaking anxiety.